The Concept of Profit Calculation from the Perspective of Islamic Economics - Fitri; Marabona Munthe (Journal of Islamic Banking, Economics and Finance, 2026)
The concept of profit calculation in Islamic economics is fundamentally different from that of conventional economics, as it is guided not only by financial outcomes but also by ethical, legal, and social considerations based on Sharia principles. This study aims to examine the concept, principles, and mechanisms of profit calculation from the perspective of Islamic economics. In Islam, profit is recognized as a legitimate return for risk-taking, effort, and investment, provided it is earned through lawful (halal) business activities and free from prohibited elements such as riba (interest), gharar (excessive uncertainty), and maysir (gambling). Profit calculation must be based on fairness, transparency, honesty, and mutual consent between parties. Furthermore, Islamic economics emphasizes the balance between profit maximization and social responsibility, ensuring that business activities contribute to public welfare (maslahah). The study uses a qualitative descriptive approach based on literature analysis of classical and contemporary Islamic economic sources. The findings indicate that profit in Islamic economics is not merely an economic surplus but also a moral and social instrument that reflects justice and accountability before society and God. Therefore, profit calculation in Islamic economics integrates material, ethical, and spiritual dimensions to achieve sustainable and equitable economic development.